Resiliensi Akademik Tanpa Regulasi Emosi? Eviden dari Mahasiswa Baru Fisioterapi - Atik Ulinuha; Alfinuha, Setyani (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
The transition from secondary education to higher education requires first-year students to adapt to various academic and psychological challenges. Within the context of health education, which is characterized by demanding academic workloads and professional expectations, academic resilience and emotion regulation are considered important factors in facilitating successful adaptation. This study aimed to explore the levels of academic resilience and emotion regulation difficulties, as well as the relationship between these variables among first-year physiotherapy students. A quantitative descriptive-correlational design was employed involving 17 first-year physiotherapy students at the Institut Ilmu Kesehatan Bhakti Wiyata Kediri, Indonesia. Data were collected using the Academic Resilience Scale-6 (ARS-6) and the Difficulties in Emotion Regulation Scale (DERS). Descriptive statistics and Pearson correlation analysis were used to analyze the data. The findings revealed that most participants demonstrated a high level of academic resilience (65%), while the majority reported a moderate level of emotion regulation difficulties (71%). Furthermore, the correlation analysis indicated no significant relationship between emotion regulation difficulties and academic resilience (r = .133, p = .611). These findings suggest that first-year physiotherapy students’ ability to cope with academic demands is not directly associated with their difficulties in regulating emotions. The results further imply that academic resilience during the early stage of university study may be influenced by other factors, such as motivation, social support, and contextual academic demands. Therefore, student support programs should not focus solely on emotional aspects but should also strengthen other protective factors that contribute to academic adaptation and success among health students.